Coseismic and early postseismic deformation of the 2020 Nima Mw 6.4 earthquake, central Tibet, from InSAR and GNSS observations - Liu, Xiaoli; Xia, Tao; Liu-Zeng, Jing; Deng, Debeier; Jia, Zhige; Wang, Peng; Yu, Pengfei; Wang, Wenqing (Frontiers in Earth Science, 2023)
The 2020 Mw6.4 Nima earthquake is one of the largest normal-faulting earthquakes recently occurring north of the Banggong suture zone in remote central Tibet, where geologic investigation of active faults is extremely limited. We analyze jointly InSAR and GNSS observations over 9 months after the Nima earthquake and calculate the coseismic and postseismic displacement. The optimal coseismic slip model suggests this event is the result of moderate-angle down-dip slip on a complex reversed “S-shape” three-segmented structure at fault junctions of the West Yibu-Chaka fault, the Heishi fault, and an unmapped blind fault, with a small component of left-lateral slip. The superposition of seismic waves from faults with different strikes and dips accounted for a large non-double-couple component in the long-period point-source solutions. The geodetic moment released by the mainshock is 6.4 × 1018 N⋅m, equivalent to Mw 6.42. Coseismic rupture concentrated at a depth of 4–15 km, with a peak slip of 1.36 m at 8.5 km depth. The cumulative afterslip moment within 9 months after the mainshock is 1 × 1018 N m, about 15.6% of that released by the mainshock coseismic slip. The afterslips contributed largely to the release of additional strain energy. In addition, shallow creep on the northern part of the blind fault, and deep uplift on the east normal fault system are promoted by stress perturbations. A significant proportion of down-dip coseismic slip spreading to more than 20 km beneath the surface, and deep up-slip afterslip have implications for the rheology of down-dip extension of the dipping faults in northern Tibet. Two obvious stress loading zones of more than 1 bar highlight seismic hazards in the region, especially in the junction between normal faults and ends of the large-size sinistral Riganpei-Co and Jiangai-Zangbu faults. It is necessary to forecast accurately by longer-term afterslip observation over timescales of years for the faults. Compared with previous studies, our results suggest a more complex subsurface fault geometry linking the normal and strike-slip faults and dynamic stress adjustment in this poorly-known region of Tibet.